Development of a novel extraction technique based on combination of molecular imprinted polymers and liquid membrane for biomedical and environmental applications - Nemulenzi, Ntakadzeni Olga (My University, 2008)
In this study a novel technique for extraction of biological and environmental samples was investigated. The developed technique is based on the combination of liquid membrane and molecular imprinted polymers technologies referred to as liquid membrane-molecular imprinting polymers extraction technique. As a model compound, 17β-estradiol was chosen, a hormone known to produce adverse effect in wild life and humans. A precipitation and bulk polymerization methods which produces easily, cleanly and in good yield polymers was used for the synthesis of the molecularly imprinted polymers. The model compound was extracted from aqueous sample through the hydrophobic porous membrane which was impregnated with toluene which also formed part of the acceptor solution. In the acceptor phase, the compound was re-extracted onto MIP beads which were also part of the organic phase. The selectivity of the new technique was demonstrated by extracting river water, waste water and fruit sample. In all different samples extracted clean chromatograms were obtained. The new technique therefore combines extraction and clean-up in one step. The enrichment factors were low and around one but can still be improved.